Chemical and functional properties of cell wall polymers from two cherry varieties at two developmental stages - Basanta, Maria Florencia (2013)
The cell wall polysaccharides of Regina and Sunburst cherry varieties at two developmental stages were extracted sequentially, and their changes in monosaccharide composition and functional properties were studied. The loosely-attached pectins presented a lower d-galacturonic acid/rhamnose ratio than ionically-bound pectins, as well as lower thickening effects of their respective 2% aqueous solution: the lowest Newtonian viscosity and shear rate dependence during the pseudoplastic phase. The main constituents of the cell wall matrix were covalently bound pectins probably through diferulate cross-linkings), with long arabinan side chains at the RG-I cores. This pectin domain was also anchored into the XG-cellulose elastic network. Ripening occurred with a decrease in the proportion of HGs, water extractable GGM and xylogalacturonan, and with a concomitant increase in neutral sugars. Ripening was also associated with higher viscosities and thickening effects, and to larger distribution of molecular weights. The highest firmness and compactness of Regina cherry may be associated with its higher proportion of calcium-bound HGs localized in the middle lamellae of cell walls, as well as to some higher molar proportion of NS (Rha and Ara) in covalently bound pectins. These pectins showed significantly better hydration properties than hemicellulose and cellulose network. Chemical composition and functional properties of cell wall polymers were dependent on cherry variety and ripening stage, and helped explain the contrasting firmness of Regina and Sunburst varieties.